2014
DOI: 10.1245/s10434-014-3529-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Flap Reconstruction on Perineal Wound Complications Following Ablative Surgery for Advanced and Recurrent Rectal Cancers

Abstract: This study suggests that flap reconstruction may provide some protective effect against perineal complications in patients undergoing pelvic exenteration, although this was not observed for APR. The most important determinants of perineal complications after pelvic exenteration were operative time and sacral resection, but no predictive factors for post-APR perineal outcomes were identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 20 publications
0
34
0
2
Order By: Relevance
“…46 To reduce the risk of postoperative infection and wound complications, we recommend the use of a vertical rectus abdominis flap to reconstruct the posterior soft-tissue defect in the pelvic floor. [47][48][49] There are several limitations to this study. The retrospective nature of the study limits the data we were able to collect and contains constraints on the analysis presented.…”
Section: Overall and Disease-specific Survivalmentioning
confidence: 98%
“…46 To reduce the risk of postoperative infection and wound complications, we recommend the use of a vertical rectus abdominis flap to reconstruct the posterior soft-tissue defect in the pelvic floor. [47][48][49] There are several limitations to this study. The retrospective nature of the study limits the data we were able to collect and contains constraints on the analysis presented.…”
Section: Overall and Disease-specific Survivalmentioning
confidence: 98%
“…Amongst these studies, 118 studies were excluded for the following reasons: one animal study; four studies included other tumour types; 49 studies just reported one surgical regimen or technical material; 17 studies were reviews, letters, editorials; 11 studies lacked full text or data; nine studies were non-English articles; 27 studies were case reports. Finally, 18 studies including one RCT and 17 cohort studies published between 1948 and 2017 were included in this systematic review and meta-analysis [8,11,14,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40].…”
Section: Literature Search and Study Selectionmentioning
confidence: 99%
“…Additionally, for the overall population, there were 1990 patients (12.17%) receiving preoperative radiotherapy in the primary closure group and 425 patients (27.12%) in the myocutaneous flap closure group, with a significant difference between the two groups. Among these included studies, one performed the propensity matching analysis, four matched BMI, 12 matched comorbidities and six matched preoperative radiotherapy [8,[26][27][28][29][30][31][32][33][34][36][37][38][39][40]. Nine studies on stage of cancer had the following distribution: low tumour stage (I-II) (252 cases in primary closure, 1.54%; 101 cases in myocutaneous flap closure, 6.45%) and advanced tumour stage (III-IV) (312 cases in primary closure, 1.91%; 124 cases in myocutaneous flap closure, 7.91%) [8,26,28,30,[32][33][34]38,39].…”
Section: Study and Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flap closures have been proposed as a way to improve perineal wound healing, but their benefit has been controversial. Some prospective studies demonstrated a protective effect of flap closure for APRs and pelvic exenterations, while other studies found limited evidence for them . Overall, the current literature suggests that flap reconstruction may be useful in certain patients and should be selectively used based on the size of the perineal defect.…”
Section: Introductionmentioning
confidence: 98%